The mathematical relationship between dishware size and portion size - Pratt, Steve; Croager, E.; Rosenberg, M. (2012)
Portion size has increased considerably over the past few decades and one influencing factor is dishware size. Using mathematical models we investigated how dish size affects the potential energy available in a meal. Two types of plate filling – flat and conical – were modelled for a range of plate sizes and energy densities, then compared to recommended daily energy requirements from Australian guidelines. Bowl filling was also modelled. Results indicate that a small increase in dishware size can lead to a substantial increase in energy available to be consumed, particularly if food is energy dense. This reinforces the need to consider dishware size when developing strategies to prevent over-consumption.